SEBUAH STUDI TENTANG KOMUNIKASI RITUAL DALAM TARIAN SEBLANG BANYUWANGI - Prihastuti, Dinar; Laturrakhmi, Yun Fitrahyati (Studi Budaya Nusantara, 2017)
ABSTRACT Several studies have been conducted to explore some practices of ritual communication in various traditions in Indonesia. However, those studies have not analysed the historical dimension of the ritual. The aim of this research is to explore the shared meaning about Tarian Seblang in the Olehsari people’s, Banyuwangi through ritual communication lens. Furthermore, the study also is conducted to reveal modified practices in Tarian Seblang which has been performed since Hindu era. Through an ethnographical study, the result of this study shows that Tarian Seblang is interpreted as an expressing gratitude to God, as an act to preventing some disaster and plagues, also as an honour to the ancestors. In the historical dimensions, this research reveals some modified practices within the ritual according to the cultural practices in Hindu era, Islamic era and the contemporary era. Some cultural practices also indicate the acculturation between Hindu values and Islamic values. The promotional efforts toward Tarian Seblang organized by the local government are considered to diminish the sacred value of this ritual.